Criminal responsibility for medical treatment provided without a patient’s consent (selected aspects) - Liszewska, Agnieszka (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
The aim of this study is to present the issues of binding force statement of intent expressing objection to taking saving life actions in case of such a need in the future. This problem becomes current when a patient is unconscious and they cannot express their will basing on an assessment of all of the circumstances regarding their health. In the study the current legal status and judicature are being analysed. The analysis leads to the conclusion that the lack of legal regulations in Poland concerning the so-called statements pro futuro precludes a doctor from making a right assessment of his duties in the context of criminal responsibility for their negligence. It concerns both a duty to act and a negligence of life or health saving actions. The lack of legal criteria assessments of a doctor’s responsibility in the context of criminal responsibility for their negligence precludes from acknowledging statements pro futuro as obliging to negligence of treatment. The Polish law guarantees the patient the right to the self – determination in insufficient way but the constitutional principle of specificity of an offence (nullum crimen sine lege) does not give a permission to attribute criminal responsibility to the doctor for performing intervention despite the existence of such a statement, because the prohibition of undertaking the medical interventions in case of an objection raised before occurrence of the situation that needs such an intervention must have a source in the binding rules.